'Smartening' anticancer therapeutic nanosystems using biomolecules. (December 2015) - Núñez-Lozano, Rebeca; Cano, Manuel; Pimentel, Belén; de la Cueva-Méndez, Guillermo
Graphical abstract: Highlights: Achieving highly selective cancer cell killing using chemotherapy has revealed more difficult than anticipated. Drug delivery systems could minimize off-target toxicity of chemotherapy, though they must overcome multiple physiological barriers to achieve this. Biomolecules can be used to transform bare nanoparticles into smart therapeutic nanosystems that sort out those barriers effectively. Abstract : To be effective, anticancer agents must induce cell killing in a selective manner, something that is proving difficult to achieve. Drug delivery systems could help to solve problems associated with the lack of selectivity of classical chemotherapeutic agents. However, to realize this, such systems must overcome multiple physiological barriers. For instance, they must evade surveillance by the immune system, attach selectively to target cells, and gain access to their interior. Furthermore, there they must escape endosomal entrapment, and release their cargoes in a controlled manner, without affecting their functionality. Here we review recent efforts aiming at using biomolecules to confer these abilities to bare nanoparticles, to transform them into smart anticancer therapeutic nanosystems.